К процессу возбуждения асинхронных генераторов - Марков, Владислав Сергеевич; Поляков, Игорь Владимирович (НТУ "ХПИ", 2015)
Статья посвящена проблеме возбуждения асинхронных генераторов. Рассматривается традиционный подход к процессу самовозбуждения и, самовозбуждение, как автоколебательный процесс в системе асинхронный двигатель-конденсатор, что позволяет уменьшить мощность возбуждения или емкость конденсаторов возбуждения. Рассматривается влияние взаимной индуктивности обмоток статора и ротора на процесс самовозбуждения.

At the present time a basic tendency of energetics is use of asynchronous generators as a power unit. Advantages of an asynchronous generator are operational reliability, electric network stability, but excitation of asynchronous generators requires a source of reactive power. In addition it requires a compensatory condenser at an asynchronous generator on-load operation in electric mains. The article is dedicated to the process of asynchronous generators excitation. It has been viewed a traditional approach to the process of self-excitations and, it’s like a self-oscillating process in the asynchronous generator - condenser system.It has been viewed a mutual inductance of stator and rotor coils effects on the generator self-excitation. It is possible to diminish of the condenser capacitance and excitation power of an asynchronous generator when a mutual inductance is the maximum.
To the process of asynchronous generators excitement
Keywords: самовозбуждение; компенсирующие конденсаторы; емкость конденсаторов возбуждения; мощность синхронного компенсатора; режим автоколебаний; asynchronous generator; generator self-excitation; mutual inductance; self-oscillating process